Genetic polymorphisms of the IL6 and NOD2 genes are risk factors for inflammatory reactions in leprosy. - Carolinne Sales-Marques; Cynthia Chester Cardoso; Lucia Elena Alvarado-Arnez; Ximena Illaramendi; Anna Maria Sales; Mariana de Andréa Hacker; Mayara Garcia de Mattos Barbosa; José Augusto da Costa Nery; Roberta Olmo Pinheiro; Euzenir Nunes Sarno; Antonio Guilherme Pacheco; Milton Ozório Moraes (Public Library of Science (PLoS), 2017)
The pathways that trigger exacerbated immune reactions in leprosy could be determined by genetic variations. Here, in a prospective approach, both genetic and non-genetic variables influencing the amount of time before the development of reactional episodes were studied using Kaplan-Meier survival curves, and the genetic effect was estimated by the Cox proportional-hazards regression model. In a sample including 447 leprosy patients, we confirmed that gender (male), and high bacillary clinical forms are risk factors for leprosy reactions. From the 15 single nucleotide polymorphisms (SNPs) at the 8 candidate genes genotyped (TNF/LTA, IFNG, IL10, TLR1, NOD2, SOD2, and IL6) we observed statistically different survival curves for rs751271 at the NOD2 and rs2069845 at the IL6 genes (log-rank p-values = 0.002 and 0.023, respectively), suggesting an influence on the amount of time before developing leprosy reactions. Cox models showed associations between the SNPs rs751271 at NOD2 and rs2069845 at IL6 with leprosy reactions (HRGT = 0.45, p = 0.002; HRAG = 1.88, p = 0.0008, respectively). Finally, IL-6 and IFN-γ levels were confirmed as high, while IL-10 titers were low in the sera of reactional patients. Rs751271-GT genotype-bearing individuals correlated (p = 0.05) with lower levels of IL-6 in sera samples, corroborating the genetic results. Although the experimental size may be considered a limitation of the study, the findings confirm the association of classical variables such as sex and clinical forms with leprosy, demonstrating the consistency of the results. From the results, we conclude that SNPs at the NOD2 and IL6 genes are associated with leprosy reactions as an outcome. NOD2 also has a clear functional pro-inflammatory link that is coherent with the exacerbated responses observed in these patients.